Closed extensor tendon rupture following neck fracture of the fifth metacarpal (Boxer's fracture): a case report. Issue 1 (1st January 2020) - Lardenoye, Sacha; Hannemann, Pascal F. W.; Ten Bosch, Jan A.
Abstract: Boxer's fractures are common injuries. This report describes a case of a rupture of both small finger extensor tendons, following a closed neck fracture of the fifth metacarpal bone. This complication has not been reported before and emphasizes the importance of good clinical examination to rule out additional damage.